Sjögren's syndrome: review of the literature of advances achieved to date - Falcón-Guerrero, Britto Ebert (2024)
This disease, called Sjögren's disease, is a chronic autoimmune disease characterized by the infiltration of inflammatory cells in the salivary and lacrimal glands, resulting in atrophy of acinar epithelial cells, cell death and loss of exocrine function; and women are nine times more likely than men to be affected by this condition, and systemic reactions can occur, involving practically any organ system. Pathogenesis is always difficult to achieve; but the diagnosis is based on characteristic clinical signs and symptoms and autoantibodies. This concern is what led us to carry out a review of the literature in PLOS ONE, PUBMED and GOOGLE SCHOLAR journals. The purpose of this review article is to summarize the recent literature on Sjögren's syndrome, from its pathogenesis to current treatment options.